Evaluation of leaf deposit quality between electrostatic and conventional multi-row sprayers in a trellised vineyard - Salcedo, Ramón; Llop, Jordi; Campos, Javier; Michael, Costas; Gallart, Montserrat; Ortega, Paula; Gil, Emilio (My University, 2020)
Spray application technologies for specialty crops have developed considerably in recent years with regard to improved control, reduced cost, and ability to avoid environmental contamination. For example, new developments in electrostatic sprayers have been progressively introduced as an alternative for vineyard spray applications. This study investigated the efficiency of this emerging technology in a Spanish trellis vineyard. First, a complete characterization of an electrostatic sprayer was conducted under laboratory conditions. The liquid flow rate was measured using different restrictor configurations to obtain the outgoing air velocities in the diffusers. Second, field trials were conducted in a vineyard testing, two forward speeds (5.9 and 4.7 km h−1, resulting in volume rates of 60 and 75 l ha−1, respectively) and the activated or deactivated electrostatic system. Tartrazine was used as a tracer material to evaluate the spray quality over the canopy. These results were compared with similar trials using a standard multi-row sprayer with orientable outputs at 5.9 km h−1 and 190 l ha−1. The results indicated that activated electrostatic treatments resulted in a greater amount of deposition on vegetation than the other trials. The activated system also produced a significant correlation between leaf deposition and forward speed (p ≤ 0.05). The most homogeneous results were achieved by the activated electrostatic sprayer at 5.9 km h−1 and the reference sprayer. These results suggest that electrostatic sprayers could save up to 68% of applied volume with similar or better deposition of the liquid and achieve homogeneity over the whole canopy.
Keywords: Electrostatic sprayer; Hydro-pneumatic system; Efficiency; Product distribution; Viticulture